Insights into transcription factors controlling strawberry fruit development and ripening - Sánchez-Gómez, Carlos; Posé, David; Martín-Pizarro, Carmen (Frontiers in Plant Science, 2022)
Fruit ripening is a highly regulated and complex process involving a series of physiological and biochemical changes aiming to maximize fruit organoleptic traits to attract herbivores, maximizing therefore seed dispersal. Furthermore, this process is of key importance for fruit quality and therefore consumer acceptance. In fleshy fruits, ripening involves an alteration in color, in the content of sugars, organic acids and secondary metabolites, such as volatile compounds, which influence flavor and aroma, and the remodeling of cell walls, resulting in the softening of the fruit. The mechanisms underlying these processes rely on the action of phytohormones, transcription factors and epigenetic modifications. Strawberry fruit is considered a model of non-climacteric species, as its ripening is mainly controlled by abscisic acid. Besides the role of phytohormones in the regulation of strawberry fruit ripening, a number of transcription factors have been identified as important regulators of these processes to date. In this review, we present a comprehensive overview of the current knowledge on the role of transcription factors in the regulation of strawberry fruit ripening, as well as in compiling candidate regulators that might play an important role but that have not been functionally studied to date.